Defining control of HIV epidemics. Issue 11 (November 2018) - Galvani, Alison P; Pandey, Abhishek; Fitzpatrick, Meagan C; Medlock, Jan; Gray, Glenda E
Summary: Although the HIV pandemic remains a global crisis, much progress has been made in implementing programmes to treat and prevent HIV infection. To guide prioritisation of efforts, the metric by which a country can declare its HIV epidemic as controlled has become increasingly relevant. Herein, we evaluate the merits of the four control criteria proposed by UNAIDS: percentage reduction in incidence over time; ratio of incidence to mortality; ratio of incidence to prevalence; and annual incidence. Using a transmission model to generate projections of demography, incidence, and mortality, we highlight potential pitfalls associated with each of the first three criteria. A definition of control based on annual incidence would provide clarity and consistency across settings.